Immunohistochemical analysis of FOXP3+ regulatory T cells in healthy human skin and autoimmune dermatoses. (22nd August 2013) - Terras, Sarah; Gambichler, Thilo; Moritz, Rose K. C.; Altmeyer, Peter; Lambert, Jo
Abstract Background Regulatory T cells (Tregs) play an important role in autoimmune diseases. In skin, the presence of Tregs is thought to be mandatory for suppression of autoreactive T cells. Here, we assess the number of Tregs in skin of healthy subjects and patients with an autoimmune dermatosis. Methods Immunohistochemical stainings for CD3 and FOXP3 on skin biopsies of healthy subjects and subjects with psoriasis, vitiligo, pemphigus vulgaris, bullous pemphigoid, and halo nevus to assess the number of T and regulatory T cells, respectively. Results Low numbers of CD3+ and FOXP3+ cells were seen in the skin of healthy controls (median = 0.5%). A significantly higher frequency of Tregs was seen in lesional skin of patients with psoriasis (median = 12.4%) and patients with bullous pemphigoid (median = 10.1%) as compared to controls. In vitiligo (median = 0.0%), pemphigus vulgaris (median = 5.2%), and halo nevi (median = 5.4%), no significant difference in number of FOXP3+ cells was observed when compared to controls. Conclusions As confirmed in the literature, few Tregs were seen in healthy skin. A high number of Tregs were present in lesional skin from patients with psoriasis and bullous pemphigoid. These results support the hypothesis that not a decrease in number but rather a decrease in function of Tregs would be at the basis of autoimmune skin diseases, which could result in unrestrained activation autoreactive T cells in skin of patients with autoimmune dermatoses.